Bottom filling glue for inhibiting filler sedimentation and preparation method thereof and chip packaging structure

By adding ion trapping agent to the underfill glue of the chip package to capture copper ions, the filler settlement problem is solved, achieving a more uniform packaging and higher reliability.

CN118879253BActive Publication Date: 2024-12-27WUHAN CHOICE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411355100.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In chip packaging, the filler particles in the bottom filler have negative charges, which repels from the copper pole in the copper-tin primary battery, causing the filler to settle and affect the overall performance of the packaging.

Method used

Using a bottom filler including filler, epoxy resin, curing agent, carbon black, accelerator and ion capture agent, the copper ions are captured by the ion capture agent, and the formation of the original battery is inhibited, thereby inhibiting the settling of the filler and improving the packaging. reliability.

Benefits of technology

It effectively suppresses the settlement of fillers, ensures the uniform distribution and consistent performance of the underfill glue, and improves the quality and reliability of chip packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118879253B_ABST
    Figure CN118879253B_ABST
Patent Text Reader

Abstract

The present invention provides a bottom filling glue for inhibiting the sedimentation of fillers, a preparation method thereof and a chip packaging structure. The bottom filling glue includes the following components by mass percentage: 58% to 70% filler, 21% to 27% epoxy resin, 10% to 14% curing agent, 0.1% to 0.2% carbon black, 0.2% to 0.4% accelerator, and 0.1% to 0.3% ion capture agent; firstly, the epoxy resin and the ion capture agent are mixed so that the ion capture agent can be evenly dispersed in the epoxy resin to obtain a premix; then, other components are added to the premix so that the raw material components can be fully mixed, and after dispersion treatment by a three-roll grinder and vacuum degassing, a bottom filling glue with uniform dispersion and stable fluidity is obtained. When the bottom filling glue provided by the present invention is used to fill and encapsulate the chip, the glue liquid can be evenly distributed in the chip and the substrate, and the formation of the primary battery is inhibited by the ion capture agent, thereby preventing the sedimentation of the filler, and after curing, it has excellent heat resistance and strong adhesion to the substrate and the chip.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chip packaging, and particularly relates to a bottom filling glue for inhibiting filler sedimentation, a preparation method thereof, and a chip packaging structure. Background Art

[0002] In advanced chip packaging technology, copper pillar bump bonding is usually used instead of traditional wire bonding to achieve electrical interconnection between the chip and the substrate and increase the number of I / O ports. The copper pillar bump is usually composed of two parts: a copper pillar and a lead-free solder with a high tin content, which is easy to form a copper-tin primary battery. When the bottom filler is used for filling and packaging, the filler particles contained in it usually have a negative charge and repel the copper electrode in the copper-tin primary battery. The filler particles move toward the tin electrode end, which causes the filler to settle, affecting the overall performance of the bottom filler.

[0003] Therefore, how to provide a bottom filling glue that inhibits the sedimentation of fillers, inhibit the formation of copper-tin primary cells by adding ion capture agents, and then inhibit the sedimentation of fillers is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0004] The object of the present invention is to provide a bottom filling glue for inhibiting filler sedimentation and a preparation method thereof and a chip packaging structure, so as to solve at least one of the above technical problems.

[0005] To achieve the above-mentioned purpose, the first aspect of the present invention provides a bottom filling glue for inhibiting filler sedimentation, wherein the bottom filling glue comprises the following components by mass percentage: 58% to 70% filler, 21% to 27% epoxy resin, 10% to 14% curing agent, 0.1% to 0.2% carbon black, 0.2% to 0.4% accelerator, and 0.1% to 0.3% ion capture agent.

[0006] In the first aspect, the filler is spherical silica.

[0007] In the first aspect, the particle size of the spherical silica is 0.5 to 3 μm.

[0008] In the first aspect, the epoxy resin consists of bisphenol A epoxy resin and high-purity low-chlorine liquid epoxy resin.

[0009] In the first aspect, the curing agent is an amine curing agent, and the amine curing agent includes at least one of a polyether amine and a modified fatty amine curing agent.

[0010] In the first aspect, the accelerator includes at least one of a tertiary amine accelerator and an imidazole accelerator.

[0011] In the first aspect, the model of the ion capture agent includes at least one of IXEPLAS-A1, IXEPLAS-A2, IXE-100 and IXE-700F.

[0012] The second aspect of the present invention provides a method for preparing a bottom filling glue that inhibits filler sedimentation as described in the first aspect, the preparation method comprising: accurately weighing each component of the raw material, wherein the components specifically include, by mass percentage: 58% to 70% filler, 21% to 27% epoxy resin, 10% to 14% curing agent, 0.1% to 0.2% carbon black, 0.2% to 0.4% accelerator, and 0.1% to 0.3% ion capture agent; adding the weighed epoxy resin and the ion capture agent to a stirring cup, stirring evenly by a first centrifugal stirrer to obtain a premix; adding the weighed filler, the curing agent, the carbon black and the accelerator to the premix, stirring evenly by a second centrifugal stirrer to obtain a first slurry; transferring the first slurry to a three-roll grinder for dispersion treatment to obtain a uniformly dispersed second slurry; vacuum degassing the second slurry by a third centrifugal stirring to obtain a bottom filling glue.

[0013] In the second aspect, the working parameters of the first centrifugal mixer include: stirring time of 55 to 65 s, rotation of 750 r / min, and revolution of 950 r / min; the working parameters of the second centrifugal mixer include: stirring time of 75 to 100 s, rotation of 1000 r / min, and revolution of 1250 r / min; the working parameters of the three-roll grinder include: feeding gap of 20 to 35 μm, and discharging gap of 10 to 15 μm; the working parameters of the third centrifugal mixer include: vacuum degassing time of 65 to 85 s, rotation of 1000 r / min, and revolution of 1250 r / min.

[0014] The third aspect of the present invention provides a chip packaging structure, which includes a substrate, a chip flipped on the substrate, a solder mask covering the substrate, and a bottom filling glue that inhibits filler sedimentation as described in the first aspect; wherein the bottom filling glue fills the bottom of the chip and partially covers the solder mask.

[0015] Beneficial effects:

[0016] The present invention provides an underfill glue for inhibiting the sedimentation of fillers, which comprises the following components by mass percentage: 58% to 70% filler, 21% to 27% epoxy resin, 10% to 14% curing agent, 0.1% to 0.2% carbon black, 0.2% to 0.4% accelerator, and 0.1% to 0.3% ion capture agent; the epoxy resin is used as the matrix resin, the epoxy resin and the ion capture agent are evenly mixed, and then mixed with the filler, the curing agent, the accelerator and the carbon black to prepare the underfill glue; during the filling process of the underfill glue, the filler in the underfill glue is passed through It often carries a negative charge and is easily repelled by the copper pole in the local galvanic cell formed by the copper column bump in the chip packaging structure, which leads to the sedimentation of the filler. The bottom filling glue is unevenly distributed during the filling process, and the performance of the bottom filling glue after curing is inconsistent at various locations, thereby affecting the quality and reliability of the chip packaging structure. The present invention captures copper ions by adding an ion capture agent to the bottom filling glue, thereby inhibiting the formation of the galvanic cell and thus inhibiting the sedimentation of the filler in the bottom filling glue. In addition, the ion capture agent can also capture impurity ions in the bottom filling glue, thereby improving the reliability of the bottom filling glue packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of this specification or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 A flow chart of a method for preparing a bottom filling adhesive for inhibiting filler sedimentation provided by the present invention;

[0019] Figure 2 This is a diagram showing the effect of sedimentation in Comparative Example 1 of the present invention;

[0020] Figure 3 This is a rendering of the effect of no settlement in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0022] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0023] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or obtained by existing methods.

[0024] The present invention provides a bottom filling glue for inhibiting filler sedimentation. The bottom filling glue comprises the following components by mass percentage: 58% to 70% filler, 21% to 27% epoxy resin, 10% to 14% curing agent, 0.1% to 0.2% carbon black, 0.2% to 0.4% accelerator, and 0.1% to 0.3% ion capture agent.

[0025] Specifically, the present invention provides a bottom filling glue for inhibiting the sedimentation of fillers, which comprises the following components by mass percentage: 58% to 70% filler, 21% to 27% epoxy resin, 10% to 14% curing agent, 0.1% to 0.2% carbon black, 0.2% to 0.4% accelerator, and 0.1% to 0.3% ion capture agent; epoxy resin is used as a base resin, the epoxy resin and the ion capture agent are mixed evenly, and then mixed with the filler, the curing agent, the accelerator and the carbon black to prepare the bottom filling glue; during the filling process of the bottom filling glue, the bottom filling glue in the bottom filling glue The filler usually carries a negative charge, and is easily repelled by the copper pole in the local galvanic cell formed by the copper column bump in the chip packaging structure, which leads to the sedimentation of the filler. The bottom filling glue is unevenly distributed during the filling process, and the performance of the bottom filling glue after curing is inconsistent at various locations, thereby affecting the quality and reliability of the chip packaging structure. The present invention captures copper ions by adding an ion capture agent to the bottom filling glue, thereby inhibiting the formation of galvanic cells and thus inhibiting the sedimentation of the filler in the bottom filling glue. In addition, the ion capture agent can also capture impurity ions in the bottom filling glue, thereby improving the reliability of the bottom filling glue packaging.

[0026] In some possible embodiments, the filler is spherical silica.

[0027] In some possible embodiments, the particle size of the spherical silica is 0.5-3 μm.

[0028] Those skilled in the art will appreciate that selecting spherical silica as a filler can reduce the thermal expansion coefficient and hygroscopicity of the bottom filler and enhance the modulus of the bottom filler; at the same time, controlling the particle size of the spherical silica to 0.5 to 3 μm can improve the dispersibility of the filler in the epoxy resin.

[0029] In some possible embodiments, the epoxy resin consists of bisphenol A epoxy resin and high-purity low-chlorine liquid epoxy resin.

[0030] This is because, by selecting bisphenol A epoxy resin and high-purity low-chlorine liquid epoxy resin as the matrix resin, the bonding performance and mechanical properties of the bottom filling glue can be improved, and the cross-linking degree of the bottom filling glue can be improved during the cross-linking and curing process by the mutual cooperation of the two epoxy resins. Preferably, the model of the bisphenol A epoxy resin is 0176 or YLE-1300A, and the model of the high-purity low-chlorine liquid epoxy resin is LX-01 or LX-02F.

[0031] In some possible embodiments, the curing agent is an amine curing agent, and the amine curing agent includes at least one of a polyether amine and a modified fatty amine curing agent.

[0032] Those skilled in the art can understand that when the glue liquid fills the bottom of the chip, the glue liquid and the chip are placed at high temperature, and the amine curing agent reacts with the epoxy resin, so that the two epoxy resins are cross-linked to form a three-dimensional network structure compound to improve the strength of the bottom filling glue. Preferably, the model of the polyether amine is D220, the model of the modified amine curing agent is SH-3823-36, and the model of the modified fatty amine curing agent is SH-3170F.

[0033] In some possible embodiments, the accelerator includes at least one of a tertiary amine accelerator and an imidazole accelerator.

[0034] This is because, in the present application, the accelerator is equivalent to a catalyst, which can promote the cross-linking and curing reaction between the amine curing agent and the epoxy resin to reduce the curing time of the glue and improve the efficiency of chip packaging. Preferably, the model of the tertiary amine accelerator is K54, and the imidazole accelerator can be 1-ethylimidazole (EMI).

[0035] In some possible embodiments, the model of the ion capture agent includes at least one of IXEPLAS-A1, IXEPLAS-A2, IXE-100 and IXE-700F.

[0036] Those skilled in the art can understand that the ion capture agent used in the present application is a submicron material with a large specific surface area, has a good capture effect on copper ions, and interacts with copper ions to form a stable inclusion complex, thereby inhibiting the formation of a primary battery in the bottom filling glue during the filling process and avoiding the sedimentation of the filler; at the same time, the ion capture agent can also capture other impurity ions to improve the reliability of chip packaging, and the ion capture agent has excellent heat resistance, which can improve the heat resistance of the bottom filling glue and further improve the stability of chip packaging. Preferably, the ion capture agent of the present application can select the following models: IXEPLAS-A1 (500nm), IXEPLAS-A2 (200nm), IXE-100 (800nm), IXE-700F (900nm).

[0037] Based on a general inventive concept, see Figure 1 The second aspect of the present invention provides a method for preparing a bottom filling glue for inhibiting filler sedimentation as described in the first aspect, the preparation method comprising:

[0038] S1. Accurately weigh the raw material components, wherein the components include, by mass percentage, 58% to 70% filler, 21% to 27% epoxy resin, 10% to 14% curing agent, 0.1% to 0.2% carbon black, 0.2% to 0.4% accelerator, and 0.1% to 0.3% ion capture agent;

[0039] S2, adding the weighed epoxy resin and the ion capture agent into a stirring cup, and stirring evenly by a first centrifugal stirrer to obtain a premix;

[0040] S3, adding the weighed filler, the curing agent, the carbon black and the accelerator to the premix, and stirring evenly by a second centrifugal stirrer to obtain a first slurry;

[0041] S4, transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry;

[0042] S5. Performing vacuum degassing on the second slurry through a third centrifugal stirring to obtain a bottom filling adhesive.

[0043] In combination with the second aspect of the present application, the working parameters of the first centrifugal mixer include: stirring time of 55 to 65s, rotation of 750r / min, and revolution of 950r / min; the working parameters of the second centrifugal mixer include: stirring time of 75 to 100s, rotation of 1000r / min, and revolution of 1250r / min; the working parameters of the three-roll grinder include: feeding gap of 20 to 35μm, and discharging gap of 10 to 15μm; the working parameters of the third centrifugal mixer include: vacuum degassing time of 65 to 85s, rotation of 1000r / min, and revolution of 1250r / min.

[0044] The present invention provides a method for preparing a bottom filling glue that inhibits the sedimentation of fillers. First, weigh each raw material component according to a specific formula ratio; second, first mix the epoxy resin and the ion capture agent so that the ion capture agent can be evenly dispersed in the epoxy resin, and fully mix the two epoxy resins to obtain a premix; then, add other components to the premix so that the raw material components can be fully mixed to obtain a first slurry for subsequent cross-linking and curing reactions; finally, transfer the evenly mixed first slurry to a three-roll grinder for dispersion treatment to further improve the compatibility between the raw material components, and perform vacuum degassing treatment to remove the gas generated during the mixing process to obtain a bottom filling glue with uniform dispersion and stable fluidity. When the bottom filling glue provided by the present application is used to fill and encapsulate the chip, the glue can be evenly distributed in the chip and the substrate, and the formation of the primary battery is inhibited by the ion capture agent, thereby preventing the sedimentation of the filler, and after curing, it is not easy to shrink in volume, and has excellent heat resistance.

[0045] Based on a general inventive concept, the third aspect of the present invention provides a chip packaging structure, which includes a substrate, a chip flipped on the substrate, a solder mask covering the substrate, and a bottom filling glue that inhibits filler sedimentation as described in the first aspect; wherein the bottom filling glue fills the bottom of the chip and partially covers the solder mask.

[0046] Specifically, the present invention provides a chip packaging structure, including a substrate, a chip flipped on the substrate, and a solder mask covering the substrate, wherein a plurality of copper pillar bumps are arranged at intervals on the solder mask, and the copper pillar bumps are composed of two parts: a copper pillar and a lead-free solder with a high tin content. In advanced packaging technology, copper pillar bumps are used instead of traditional wire bonding to achieve electrical interconnection between the chip and the substrate, which is suitable for narrow-section matrix interconnection and increases the number of I / O ports. The copper pillar bumps are arranged between the chip and the substrate to connect the chip and the substrate, thereby forming a gap between the chip, the substrate and the copper pillar bumps, and the gap is filled with the bottom filling glue prepared above, and after curing, a chip packaging structure is formed.

[0047] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0048] Example 1

[0049] In terms of mass percentage, the raw materials of the bottom filler include:

[0050] Filler: 63%, epoxy resin YLE-1300A: 12%, epoxy resin LX-02F: 12%, curing agent SH-3170F: 12.5%, carbon black: 0.15%, accelerator EMI: 0.25%, ion capture agent IXEPLAS-A2: 0.1%;

[0051] The specific steps of preparing the above bottom filling are as follows:

[0052] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0053] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 55 s, and mix them evenly to obtain a premix;

[0054] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 75 s, and mix well to obtain a first slurry;

[0055] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 20 μm, and the discharge gap is set to 10 μm;

[0056] (5) The vacuum degassing time of the third centrifugal mixer is set to 65 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0057] Example 2

[0058] In terms of mass percentage, the raw materials of the bottom filler include:

[0059] Filler: 63%, epoxy resin YLE-1300A: 12%, epoxy resin LX-02F: 12%, curing agent SH-3170F: 12.5%, carbon black: 0.15%, accelerator EMI: 0.25%, ion capture agent IXEPLAS-A1: 0.1%;

[0060] The specific steps of preparing the above bottom filling are as follows:

[0061] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0062] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 65 s, and mix them evenly to obtain a premix;

[0063] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 100 s, and mix them evenly to obtain a first slurry;

[0064] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 35 μm, and the discharge gap is set to 15 μm;

[0065] (5) The vacuum degassing time of the third centrifugal mixer is set to 85 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0066] Example 3

[0067] In terms of mass percentage, the raw materials of the bottom filler include:

[0068] Filler: 63%, epoxy resin YLE-1300A: 12%, epoxy resin LX-02F: 12%, curing agent SH-3170F: 12.5%, carbon black: 0.15%, accelerator EMI: 0.25%, ion capture agent IXE-100: 0.1%;

[0069] The specific steps of preparing the above bottom filling are as follows:

[0070] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0071] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 60 s, and mix them evenly to obtain a premix;

[0072] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 90 s, and mix well to obtain a first slurry;

[0073] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 30 μm, and the discharge gap is set to 15 μm;

[0074] (5) The vacuum degassing time of the third centrifugal mixer is set to 75 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0075] Example 4

[0076] In terms of mass percentage, the raw materials of the bottom filler include:

[0077] Filler: 63%, epoxy resin YLE-1300A: 12%, epoxy resin LX-02F: 12%, curing agent SH-3170F: 12.5%, carbon black: 0.15%, accelerator EMI: 0.25%, ion capture agent IXE-700F: 0.1%;

[0078] The specific steps of preparing the above bottom filling are as follows:

[0079] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0080] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 60 s, and mix them evenly to obtain a premix;

[0081] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 80 s, and mix well to obtain a first slurry;

[0082] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 25 μm, and the discharge gap is set to 15 μm;

[0083] (5) The vacuum degassing time of the third centrifugal mixer is set to 70 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0084] Example 5

[0085] In terms of mass percentage, the raw materials of the bottom filler include:

[0086] Filler: 63%, epoxy resin 0176: 13%, epoxy resin LX-01: 13%, curing agent D220: 10.5%, carbon black: 0.1%, accelerator EMI: 0.2%, ion capture agent IXEPLAS-A2: 0.2%;

[0087] The specific steps of preparing the above bottom filling are as follows:

[0088] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0089] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 60 s, and mix them evenly to obtain a premix;

[0090] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 80 s, and mix well to obtain a first slurry;

[0091] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 30 μm, and the discharge gap is set to 15 μm;

[0092] (5) The vacuum degassing time of the third centrifugal mixer is set to 85 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0093] Example 6

[0094] In terms of mass percentage, the raw materials of the bottom filler include:

[0095] Filler: 63%, epoxy resin YLE-1300A: 12%, epoxy resin LX-02F: 11%, curing agent SH-3823-36: 13.3%, carbon black: 0.15%, accelerator K54: 0.25%, ion capture agent IXEPLAS-A2: 0.3%;

[0096] The specific steps of preparing the above bottom filling are as follows:

[0097] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0098] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 60 s, and mix them evenly to obtain a premix;

[0099] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 95 s, and mix well to obtain a first slurry;

[0100] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 20 μm, and the discharge gap is set to 10 μm;

[0101] (5) The vacuum degassing time of the third centrifugal mixer is set to 80 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0102] Comparative Example 1

[0103] In terms of mass percentage, the raw materials of the bottom filler include:

[0104] Filler: 63%, epoxy resin 0176: 12%, epoxy resin LX-01: 12%, curing agent D220: 12.5%, carbon black: 0.15%, accelerator K54: 0.35%;

[0105] The specific steps of preparing the above bottom filling are as follows:

[0106] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0107] (2) Add the weighed filler, epoxy resin, curing agent, carbon black and accelerator into a stirring cup, set the second centrifugal stirrer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 75 s, and mix them evenly to obtain a first slurry;

[0108] (3) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 20 μm, and the discharge gap is set to 10 μm;

[0109] (4) The vacuum degassing time of the third centrifugal mixer is set to 65 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0110] Comparative Example 2

[0111] In terms of mass percentage, the raw materials of the bottom filler include:

[0112] Filler: 63%, epoxy resin 0176: 12%, epoxy resin LX-01: 12%, curing agent D220: 12%, carbon black: 0.15%, accelerator K54: 0.35%, ion capture agent IXEPLAS-A1: 0.5%;

[0113] The specific steps of preparing the above bottom filling are as follows:

[0114] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0115] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 55 s, and mix them evenly to obtain a premix;

[0116] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 75 s, and mix well to obtain a first slurry;

[0117] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 20 μm, and the discharge gap is set to 10 μm;

[0118] (5) The vacuum degassing time of the third centrifugal mixer is set to 65 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0119] Comparative Example 3

[0120] In terms of mass percentage, the raw materials of the bottom filler include:

[0121] Filler: 71%, epoxy resin YLE-1300A: 10%, epoxy resin LX-01: 10%, curing agent SH-3823-36: 8.3%, carbon black: 0.15%, accelerator EMI: 0.35%, ion capture agent IXEPLAS-A1: 0.2%;

[0122] The specific steps of preparing the above bottom filling are as follows:

[0123] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0124] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 55 s, and mix them evenly to obtain a premix;

[0125] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 75 s, and mix well to obtain a first slurry;

[0126] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 20 μm, and the discharge gap is set to 10 μm;

[0127] (5) The vacuum degassing time of the third centrifugal mixer is set to 65 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0128] Comparative Example 4

[0129] In terms of mass percentage, the raw materials of the bottom filler include:

[0130] Filler: 57%, epoxy resin 0176: 14%, epoxy resin LX-01: 14%, curing agent SH-3170F: 14.3%, carbon black: 0.15%, accelerator EMI: 0.35%, ion capture agent IXEPLAS-A2: 0.2%;

[0131] The specific steps of preparing the above bottom filling are as follows:

[0132] (1) Weigh each component according to the mass percentage of each component of the above-mentioned bottom filling glue raw material;

[0133] (2) Add the weighed epoxy resin and ion scavenger into a stirring cup, set the first centrifugal stirrer to rotate at 750 r / min, revolve at 950 r / min, and stir for 55 s, and mix them evenly to obtain a premix;

[0134] (3) Add the weighed filler, curing agent, carbon black and accelerator to the premix, set the second centrifugal mixer to rotate at 1000 r / min, revolve at 1250 r / min, and stir for 75 s, and mix well to obtain a first slurry;

[0135] (4) transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein the feed gap of the three rollers in the three-roll mill is set to 20 μm, and the discharge gap is set to 10 μm;

[0136] (5) The vacuum degassing time of the third centrifugal mixer is set to 65 seconds, the rotation speed is 1000 r / min, and the revolution speed is 1250 r / min. The second slurry is vacuum degassed by the third centrifugal mixer to obtain the bottom filling glue.

[0137] The bottom filling glue provided in Examples 1-6 and Comparative Examples 1-4 was subjected to flowability test, sedimentation test, glass transition temperature Tg, ion content, conductivity and reliability test. The specific test process is as follows:

[0138] 1. Test method for fluidity: Place a 15×25 mm silicon wafer with copper pillars on the PCB and fix it. Place it on a 110°C hot plate and preheat it for one minute. Use a dispenser to dispense (40-45) mg of the bottom filler to be tested along the long side of the silicon wafer. Under the action of capillary force, the bottom filler will flow to the bottom of the silicon wafer. Record the time it takes to fill the entire silicon wafer.

[0139] 2. Sedimentation test: After the fluidity test, slice and polish the sample after it is completely cured, and observe whether there is filler sedimentation under an ultrasonic scanning microscope;

[0140] 3. Glass transition temperature Tg: Reference standard: ASTM E2254-2018, take a fully cured sample, prepare a test sample with a size of 55mm×10mm×3mm, measurement mode: dual cantilever mode, vibration frequency: 1Hz, amplitude: 10μm, heating rate: 5℃ / min;

[0141] 4. Test method for ion content: Weigh 2.5±0.2g of the fully cured sample and place it in 25±2g of water. After high temperature and high pressure cooking test (PCT test: test conditions 120±2℃, 20h), take the soaking water and test the ion concentration using an ion chromatograph;

[0142] 5. Conductivity test method: Weigh 2.5±0.2g of the fully cured sample and place it in 25±2g of water. After high temperature and high pressure cooking test (PCT test: test conditions 120±2℃, 20h), take the soaking water and test the conductivity with a conductivity meter;

[0143] 6. Reliability test: The sample is cast in a pudding mold with a diameter of 3mm and a height of 2mm. One end of the cast sample is in contact with the silicon wafer. The silicon wafer and the pudding mold are fixed. After complete curing, the pudding mold is removed, the sample is taken out, and tested with a thrust machine; after a highly accelerated temperature and humidity test (Uhast test, test conditions: temperature 130℃, humidity 85%, 96h), take it out and test it with a thrust machine; the thrust machine test speed is 50μm / s, and the contact height is 20μm.

[0144] The test results are shown in Table 1 below:

[0145] Table 1 Test results

[0146]

[0147] From the above table, we can see that:

[0148] (1) In Comparative Example 1, no ion capture agent was added. After the gap was filled with the bottom filler, due to the formation of a copper-tin primary battery, the negatively charged filler moved from copper to tin, causing the filler in the bottom filler to settle and aggregate. Figure 2 As shown, the components of the bottom filling glue are unevenly distributed, and the performance of the bottom filling glue after curing is poor;

[0149] (2) Although an ion scavenger was added in Comparative Example 2, the thixotropic coefficient of the bottom filling glue was increased due to the large proportion of the added amount, resulting in poor fluidity of the glue solution;

[0150] (3) The solid content of the filler in Comparative Example 3 is too high, resulting in poor fluidity of the glue solution; the solid content of the filler in Comparative Example 4 is too low, resulting in a low glass transition temperature of the bottom filling glue after curing;

[0151] (4) From the data of Examples 2-4, it can be seen that as the particle size of the ion capture agent gradually increases, the free ion concentration and conductivity gradually increase, and the effect of ion capture becomes worse;

[0152] (5) It can be seen from the data of the comparative examples and the examples that only the bottom filling glue within a specific formula ratio has good fluidity, is not easy to settle, and has good reliability for chip packaging. The bottom filling glue prepared in Example 2 did not settle under a microscope. Figure 3 shown.

[0153] In summary, the bottom filling glue prepared by the formula ratio provided by the present invention can inhibit the sedimentation of the filler, and has good fluidity, is easy to fill the gap between the chip, the substrate and the copper column bumps, has excellent silicon adhesion after curing, can be tightly bonded to the substrate and the chip, and realizes the reliability of chip packaging.

[0154] Comparative Example 1: No ion trapping agent was used. After the chip was filled with the bottom filling glue, the filler precipitated from copper to tin due to the potential difference between copper and tin.

[0155] In the comparative example, the diion capture agent is excessive. Due to its small particle size and large specific surface area, the excessive particles are mixed in the system, filling the gaps, increasing the thixotropy of the bottom filling glue, and slowing down the flow;

[0156] The raw material dosage of comparative examples 3 and 4 is not within the optimal applicable range, and the overall performance of the bottom filling glue is poor;

[0157] The particle size of the ion capture agent in Examples 1 to 4 gradually increases, and the smaller the particle size, the better the ion capture effect; each component is within the optimal use range, the bottom filling glue has good fluidity, strong reliability and the filler does not settle.

[0158] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0159] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0160] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A bottom filling glue for inhibiting filler sedimentation, characterized in that: The bottom filling glue is composed of the following components by mass percentage: filler 63%, epoxy resin 21% to 27%, curing agent 10% to 14%, carbon black 0.1% to 0.2%, accelerator 0.2% to 0.4%, ion capture agent 0.1% to 0.3%; The filler is spherical silica; the particle size of the spherical silica is 0.5 to 3 μm; The epoxy resin is composed of bisphenol A epoxy resin and high-purity low-chlorine liquid epoxy resin; The curing agent is an amine curing agent, and the amine curing agent includes at least one of a polyetheramine and a modified fatty amine curing agent; The accelerator includes at least one of a tertiary amine accelerator and an imidazole accelerator; The ion capture agent includes at least one of IXEPLAS-A1, IXEPLAS-A2, IXE-100 and IXE-700F.

2. A method for preparing an underfill adhesive for inhibiting filler sedimentation as claimed in claim 1, characterized in that: The preparation method comprises: Accurately weigh the raw material components, which specifically include, by mass percentage, 63% filler, 21% to 27% epoxy resin, 10% to 14% curing agent, 0.1% to 0.2% carbon black, 0.2% to 0.4% accelerator, and 0.1% to 0.3% ion capture agent; Add the weighed epoxy resin and the ion capture agent into a stirring cup, and stir them evenly using a first centrifugal stirrer to obtain a premix; Adding the weighed filler, the curing agent, the carbon black and the accelerator to the premix, and stirring evenly by a second centrifugal stirrer to obtain a first slurry; Transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; The second slurry is vacuum degassed by a third centrifugal stirring to obtain a bottom filling glue; The working parameters of the first centrifugal mixer include: stirring time of 55 to 65 seconds, rotation of 750 r / min, revolution of 950 r / min; The working parameters of the second centrifugal mixer include: stirring time of 75 to 100 seconds, rotation of 1000 r / min, revolution of 1250 r / min; The working parameters of the three-roll mill include: the feed gap is 20-35 μm, the discharge gap is 10-15 μm; The working parameters of the third centrifugal mixer include: vacuum degassing time of 65 to 85 seconds, rotation of 1000 r / min, and revolution of 1250 r / min.

3. A chip packaging structure, characterized in that: The chip packaging structure includes a substrate, a chip flipped on the substrate, a solder mask covering the substrate, and a bottom filling glue for inhibiting filler sedimentation as described in claim 1; wherein the bottom filling glue fills the bottom of the chip and partially covers the solder mask.